Wage Floors and Optimal Job Design - Jenny Kragl; Anja Schöttner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We analyze the effects of lower bounds on wages, e.g., minimum wages or liability limits, on job design within firms. In our model, two tasks contribute to non-verifiable firm value and affect an imperfect performance measure. The tasks can be assigned to either one or two agents. In the absence of a wage floor, it is optimal to assign the tasks to different agents whenever the agents' reservation utility is not too large. Under such a job design, the principal can tailor incentives according to each task's marginal productivity. By contrast, with a relatively large wage floor, the principal gradually lowers effort incentives to avoid rent payments to the agents, even before the wage floor exceeds the agents' reservation utility. If the wage floor is sufficiently large, the principal hires only one agent even though this leads to a distortion of effort across tasks or the non-execution of one task altogether.
Keywords: M52; M54; D82; 330; Job Design; Moral Hazard; Multitasking; Wage Floor; Minimum Wage; Limited Liability